"Dentro y fuera". El problema del espacio "postfantástico" en la exposición de Ella imagina de Juan José Millás - Csuday, Csaba (Verbum – Analecta Neolatina, 2003)
This paper sets off with the philosophical notion of Space, with special respect to Paul Natorp's and Heidegger's definitions. Then, it goes on to observe how this philosophical approximation can be related to the monologue entitled Ella imagina 'She imagines' by the Spanish writer, Juan José Millás. The paper attempts to find out the content and the meaning of the opposition 'inside' and 'outside' in the work and to describe how it characterizes the protagonist, as the reality of text.